O aperfeiçoamento da escrita por meio da Fonologia: a estrutura silábica na escrita dos alunos do Ensino Fundamental II - Rodrigues, Amilla Barbosa (2019)
This work is based on Phonology and its theoretical studies about the syllable to deal with the phenomena of erasure and insertion in the writing of Elementary School students II. The purpose of this study was to identify unconventional writing in students of the sixth grade, through the analysis of 105 textual productions, in order to propose activities that contributed to the improvement of writing. We focused on the study of the syllable, according to the precepts of Autossegmental Phonology and the Metric Theory of Syllable to justify and treat the students' writing deviations, so that we could design and apply a didactic intervention with these students in the hope of perfecting writing and eliminate misspellings. We consider the following theoretical approaches: i) the hierarchy of the elements that make up the syllabic structure in line with the principles that govern this structure; ii) the phonological processes of insertion and erasure; iii) the relationship between orality and writing; and iv) phonological awareness. In order to do so, we return to the studies of Oliveira and Nascimento (1990), Camara Jr. (1999), Bisol (1999), Pedrosa (2007), Abaurre and Pagotto (2002), Silva (2003), Miranda and Matzenauer 2010), Volcão, Nunes and Seara (2015), Hora and Magalhães (2016), among others. The intervention proposed by this research comprises 21 Language Practices that aimed to minimize the incorrect spelling of vocabulary with segments inserted or deleted by the students. This intervention achieved positive results and revealed a smaller number of orthographic inadequacies than the initial data indicated. These results prove that the theory, in this case, the phonological theory, and the practice should be used in favor of an effectively productive teaching.